PROFILING THE PHONOLOGICAL PROCESSES SHAPING THE FOSSILISED IL OF ADULT SPANISH LEARNERS OF ENGLISH AS FOREIGN LANGUAGE. SOME THEORETICAL IMPLICATIONS. - Monroy Casas, Rafael (International Journal of English Studies, 2001)
In the ever-growing literature dealing with the acquisition by adults of the phonetics and phonology of a foreign language (FL), research has tried to provide an answer to the complex nature of cross-language transfer. The fact that despite idiosyncratic differences and sociolinguistic variation most adults learners of a foreign language (FL) speak with an accent which is a reflection of their native language (NL) and that their progress is impaired at a certain stage prompted a host of questions such as whether adults follow identical or different paths of development in their approach to a foreign language, whether those speaking the same native language are able to identify target language categories in the same way, whether perception and production are interdependent, the nature of the learning abilities and the interplay of transfer with universals. These and other problems relating to foreign language speech have been approached from different angles and theoretical frameworks (see Leather & James (1 99 1) for an overview, and more recently Leather (1999). The research reported here, based on the oral production of sixty-five Spanish adult learners of English as a FL, tries to shed some light on one of well-known problems related to the acquisition of a foreign language by non-native speakers: the analysis of different types of phonological processes shaping the fossilised interlanguage (IL) of adult FL learners in order to see a) whether they are adhered to by those adult learners sharing identical L1; b) whetherfrozen IL reflects transfer from the leamer's L1 or is the result of developmental (Le. universal) processes. In this connection we(1987) and SimilarityIDifferential Rate Hypothesis (1999) or Ekman's Markedness Differential Hypothesis (1977) and Structural Conformity Hypothesis in connection with some of the processes under analysis. Optimality Theory will be brought in in dealing with some problems encountered under Cluster Simplification. Ultimately, we shall try to explain why adult speakers of a language like Spanish tend to identi@ target categories in much the same way without necessarily having to resort in all cases to language universals as decisive factors shaping their IL. shall examine the extent to which the leamers' IL reflects the alleged tendency to reduce complex syllabic margins to a Universal Canonical Syllable Structure (UCSS). We shall alsodiscuss the explanatory power of some universal phonological models like Major's Ontogeny Model